Предмет: Алгебра,
автор: Folks228
(х2+6х-4)2-(х2-4)2=12х3+36х2+7
Ответы
Автор ответа:
0
по формуле разница квадратов :
(х^2+6х-4-(х^2-4))(х^2+6х-4+х^2-4)=12х^3+36х^2+7;
6х(2х^2+6х-8)=12х^3+36х^2+7;
12х^3+36х^2-48х-12х^3-36х^2-7=0;
48х=-7; х=-7/48.
(х^2+6х-4-(х^2-4))(х^2+6х-4+х^2-4)=12х^3+36х^2+7;
6х(2х^2+6х-8)=12х^3+36х^2+7;
12х^3+36х^2-48х-12х^3-36х^2-7=0;
48х=-7; х=-7/48.
Похожие вопросы
Предмет: Английский язык,
автор: asduorh
Предмет: Английский язык,
автор: KimArthuroff
Предмет: Математика,
автор: melnikov202008k15
Предмет: Математика,
автор: anastasiameow29
Предмет: География,
автор: denisA5